2020
DOI: 10.1007/s00428-020-02875-9
|View full text |Cite
|
Sign up to set email alerts
|

A combined histo-score based on tumor differentiation and lymphocytic infiltrate is a robust prognostic marker for mobile tongue cancer

Abstract: We wanted to evaluate the prognostic value of common histopathological variables in a large cohort of patients with cancer in the mobile tongue as such information can be important for treatment stratification of the individual patient, especially for patients with low-stage disease. In addition, we wanted to investigate whether an alternative scoring model with fewer options would compromise the prognostic value. One hundred fifty patients with oral tongue squamous cell carcinomas that were treated in curativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…OTSCC/OSCC cases with poorly differentiated phenotype have been shown to have poor prognosis. 40,41 In agreement with these observations, OTSCC cases with combined loss of CK13 and IVL expression at invading cores was significantly associated with poorer 5-year overall survival (Figure 4(E,F)). Multivariate Cox regression analysis further indicated that the combined loss of IVL and CK13 at invading core was an independent prognostic factor (HR = 0.38, CI = 0.17-0.85, p = 0.02) in OTSCC.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…OTSCC/OSCC cases with poorly differentiated phenotype have been shown to have poor prognosis. 40,41 In agreement with these observations, OTSCC cases with combined loss of CK13 and IVL expression at invading cores was significantly associated with poorer 5-year overall survival (Figure 4(E,F)). Multivariate Cox regression analysis further indicated that the combined loss of IVL and CK13 at invading core was an independent prognostic factor (HR = 0.38, CI = 0.17-0.85, p = 0.02) in OTSCC.…”
Section: Discussionsupporting
confidence: 83%
“…OTSCC/OSCC cases with poorly differentiated phenotype have been shown to have poor prognosis 40,41 . In agreement with these observations, OTSCC cases with combined loss of CK13 and IVL expression at invading cores was significantly associated with poorer 5‐year overall survival (Figure 4(E,F)).…”
Section: Discussionsupporting
confidence: 80%
“…Regarding the emerging prognostic markers that are not included in the pathology report, the published studies revealed a promising prognostic value for cancer‐related histopathologic markers including cell‐in‐cell structures (one study), 19 tumor budding (seven studies), 13,15,25–29 and pattern of invasion (15 studies) which were evaluated either as mode of invasion, 22,30 pattern of invasion, 31–34 invasive pattern, 28 or WPOI 13,16,25,35–39 . At the same time, some of the relevant studies analyzed stromal‐related histopathologic markers including stromal infiltrating lymphocytes (one study) 18 and tumor–stroma ratio (TSR; three studies) 17,40,41 which were significantly associated with prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…Most recently (2020), Bjerkli et al. proposed a histo-score based on the assessment of the lymphocytic infiltrate and tumor differentiation, and showed that the score gave a good prediction of survival in oral tongue cancer ( 14 ). Our group ( 15 ) proposed stromal classification, based on the assessment of tumor-infiltrating lymphocytes and tumor-stroma ratio, with a promising prognostic value in early oral tongue cancer.…”
Section: Assessment Of Immune Response As a Part Of Grading Systems Omentioning
confidence: 99%
“…Brandwein-Gensler et al (13) assessed the immune response as a part of a histologic risk score including three parameters: worst pattern of invasion, perineural invasion and lymphocytic host response (13). Most recently (2020), Bjerkli et al proposed a histo-score based on the assessment of the lymphocytic infiltrate and tumor differentiation, and showed that the score gave a good prediction of survival in oral tongue cancer (14). Our group (15) proposed stromal classification, based on the assessment of tumorinfiltrating lymphocytes and tumor-stroma ratio, with a promising prognostic value in early oral tongue cancer.…”
Section: Assessment Of Immune Response As a Part Of Grading Systems Of Osccmentioning
confidence: 99%